Is the reversed congruency effect unique to the eye-gaze? Investigating the effects of finger pointing, eye-gaze and arrows stimuli on spatial interference - Bonventre, Sofia; Marotta, Andrea (Frontiers in Cognition, 2023)
Spatial interference tasks have been recently used to investigate the supposed uniqueness of gaze processing and attention. For instance, it has been observed that gaze stimuli elicited faster responses when their direction was incongruent with their position ('reversed spatial congruency effect', RCE), whereas arrows produced faster reaction times (RT) when it was congruent ('standard spatial congruency effect', SCE). In the present study, we tested whether the RCE is unique to eye-gaze stimuli or can be observed in response to other important social stimuli such as pointing fingers. To this aim, congruency effects elicited by eye gaze, arrows, and pointing fingers were compared in a spatial interference task. The RCE was only observed in response to eye-gaze stimuli while pointing fingers and arrows elicited the SCE. This suggests that the RCE reversed congruency effect is specific to gaze stimuli and cannot be generalized to finger-pointing stimuli.